Re: How to transform a functional expression into a general expression

*To*: mathgroup at smc.vnet.net*Subject*: [mg119785] Re: How to transform a functional expression into a general expression*From*: DrMajorBob <btreat1 at austin.rr.com>*Date*: Wed, 22 Jun 2011 03:44:46 -0400 (EDT)

I see NO reason to call one of those equations more "general" than the other, but this may do what you want (sometimes): y == 3/2 x + 1 // Simplify Subtract @@ % == 0 2 + 3 x == 2 y 2 + 3 x - 2 y == 0 Bobby On Tue, 21 Jun 2011 07:35:58 -0500, sigismond kmiecik <sigismond.kmiecik at wanadoo.fr> wrote: > Hello to all > > I will take a simple example. > > How can you easily transform using Mathematica the following functional > expression > > y = 3/2 x + 1 > > into its general equivalent: > > 3 x - 2 y + 2 = 0 > > > This general form exists because > > y == 3/2 x + 1 // FullSimplify > > returns True. > > Is the answer given valid whatever the complexity of the initial > equality expression known to be true (with up to three unknown > variables). > > Thanks > > Sigismond Kmiecik > -- DrMajorBob at yahoo.com